The Effect of Parenting Dimensions on College Adjustment and Academic Performance: The Mediating Role of Basic Psychological Needs Satisfaction, Self-Esteem and Academic Engagement Among University Students from International Programs in Bangkok, Thailand - Khosravi, Zahra; Mohanan, Santhosh Ayathupady (Scholar: Human Sciences, 2021)
The primary objective of this study was to investigate the effect of parenting dimensions (warmth, rejection, structure, chaos, autonomy support, & coercion) on university students’ college adjustment and academic performance, being mediated by basic psychological need satisfaction, self-esteem and academic engagement. The participants of the study were 1224 university students (700 females and 524 males), aged between 18 and 25 years, who had attended international degree programs in Bangkok, Thailand. Data for the research were collected using a questionnaire survey that consisted of the following standardized scales, namely Parent as Social Context Questionnaire-Revised (PASCQ-R), Basic Psychological Needs Scale (BPNS), Rosenberg Self-Esteem Scale (RSES), the University Student Engagement (USEI), and College Adjustment Test (CAT). The proposed structural relations model was tested applying Structural Equation Modeling. The reliability and validity of the measures were established by Cronbach’s Alpha and Confirmatory Factor Analysis respectively. The results supported the proposed model’s fit in the data. Specifically, the positive parenting dimensions were found to be positively related to college adjustment and academic performance, being mediated by basic psychological needs satisfaction, self-esteem, and academic engagement. In addition, negative parenting dimensions were found to be negatively related to college adjustment and academic performance being mediated by basic psychological needs satisfaction, self-esteem, and academic engagement. The study’s limitations, implications, and avenues for further research are also discussed.